The Effect of Reflexology Massage and Oxytocin Massage on Breast Milk Adequacy Levels in Breastfeeding Mothers - Dian Nur Adkhana Sari; Usman Usman; Suryati Suryati (Indonesian Journal of Global Health Research, 2026)
Increasing breast milk supply for breastfeeding mothers aged 0-6 months is a crucial step in supporting optimal infant growth and development. Many mothers experience challenges in producing sufficient breast milk, necessitating interventions that can support successful breastfeeding. Oxytocin massage and reflexology are methods to support breast milk production, each with its own distinct mechanisms. The purpose of this study was to determine the effect of reflexology and oxytocin massage on breast milk supply in breastfeeding mothers. This research method used a pre-experimental design with a one-group pretest-posttest design. Statistical testing used the Wilcoxon test to demonstrate significant changes before and after the intervention. The p-value was used to determine differences. A sample of 40 breastfeeding mothers was divided into two intervention groups. sampling using purposive sampling technique. The results of this study, using the Wilcoxon test, showed a significant change in breast milk sufficiency before the intervention of 4.80 and after the oxytocin massage intervention of 7.56, a difference from the pre-post results of 2.85 with a p-value of 0.000 (p-value <0.005). Meanwhile, the difference between reflexology massage before and after the reflexology massage intervention was 5.55 and 7.85, a difference from the pre-post results of 2.85 with a p-value of 0.000 (p-value <0.005). This indicates that breast milk sufficiency with oxytocin massage and reflexology massage can both increase breast milk sufficiency, but there is no significant difference between the two.